Avian assemblages in lowland and foothill agro-ecosystem in Lesotho - Kopij, G. (Acta Biologica Sibirica, 2018)
During the years 1996-2001, the line transect method has been employed to assess the species composition, dominance structure and relative abundance of birds resident in traditional farmlands, in the lowlands (10 transects with the total length of 43.9 km) and foothills (10 transects with the total length of transects 46.5 km) of Lesotho, southern Africa. This has been done to show the role of this farming in biodiversity conservation. A total of 76 resident species have been recorded in farmlands of Lesotho, 62 species in the lowlands and 53 species in the foothills. In the lowland farmlands the dominant group was composed of 6 species, namely the Prinia, Cape Bunting, Cinnamon-breasted Bunting, Cape Canary, Neddicky and Common Quail (35.8 %); in the foothills the group was composed 5 species: Karoo Prinia, Cape-turtle Dove, Laughing Dove, Cape Bunting and Cape Canary (35.9 %). Eighteen species bred in significantly different densities in lowlands and foothills. While insectivorous birds were more numerous in the lowland than foothill, the reverse was true with granivorous birds. Those two guilds comprised together 78% and 83% in the lowland and foothill respectively. The proportion of species in each guild was similar. In the lowland farmland the following eight species were more common that in the foothill farmlands, while in foothill farmland 10 species were more numerous than in lowland farmland. Species diversity and evenness were strikingly high and similar in lowlands and foothills, although Sorensen Similarity Index between these two areas was low (I = 0.44). Both species diversity and structure of dominance in avian communities in Lesotho farmlands indicate that the traditional farming play a positive role in biodiversity conservation.